ISOLASI PROTEIN DAN PRODUKSI KONSENTRAT PROTEIN DAUN (KPD) SEBAGAI SUPLEMEN PAKAN TERNAK - Yatno Yatno; Suparjo Suparjo; Rasmi Murni (Udayana University, 2018)
The research aim to determine the effect of extraction using various combination of pH alkaline-acid to protein and amino acid content of Lamtoro Protein Concentrate Leaf (LPCL). Completely Randomized Design (CRD) with 3 treatments and 5 replications. The Lamtoro Leaf Meal (LLM) (50 gram) was blended in NaOH (200 ml) for 15 menit and centrifuged to separate the supernatant from extracted LLM. The extracted LLM was re-extracted with buffer acetat pH 4,6 and sentrifuged again to separate supernantant from extracted LLM. Both supernatant from NaOH and buffera acetat pH 4,6 extraction were mixed and precipitated with buffer phospat until isoelectric point. The treatments were tested consisted of extracted with NaOH pH 8, NaOH pH 9 and NaOH pH 10. The parameters measured; isoelectric point at precipited, crude protein, total amino acid (TAA), total essential amino acid (TEAA) and individual amino acid. The results showed that the precipited obtained isoelectric point pH 7 was 2.66; 1.03 and 2.58 gram at the extraction treatments using NaOH at pH 8, 9 and 10, respectively. LPCL extracted using NaOH at pH 9 and 10 contained a high crude protein of 54.82 and 52.60% higher than the extraction using NaOH at pH 8 of 46.98%. The total amount of amino acid and essential amino acid (AAE) of LPCL were highest in treatment using NaOH at pH 10 of 26,58; 13.31 %, respectively. Combination extraction LLM using pH buffer 10 followed by re-extract using acetate buffer pH 4,6 contains crude protein and good essential amino acid, especially leucine. Conclution of the research that the combination extraction using NaOH at pH 10 and followed by re-extract using acetate buffer at pH 4.6 is the best treatment contain crude protein and essential amino acid at LPCL. Keywords : Crude protein, essential amico acid, extraction.